Very High Frequency Radio Emissions Associated With the Production of Terrestrial Gamma‐Ray Flashes. Issue 4 (28th February 2018) - Lyu, Fanchao; Cummer, Steven A.; Krehbiel, Paul R.; Rison, William; Briggs, Michael S.; Cramer, Eric; Roberts, Oliver; Stanbro, Matthew
Abstract: Recent studies of the close association between terrestrial gamma‐ray flashes (TGFs) production and simultaneous lightning processes have shown that many TGFs are produced during the initial leader of intracloud flashes and that some low‐frequency (LF) radio emissions may directly come from TGF itself. Measurements of any simultaneous very high frequency (VHF) radio emissions would give important insight into any lightning leader dynamics that are associated with TGF generation, and thus, such measurements are needed. Here we report on coordinated observations of TGFs detected simultaneously by Fermi Gamma‐ray Burst Monitor, two VHF lightning mapping arrays, and Duke ground‐based LF radio sensors to investigate more on the close association between TGFs and LF and VHF radio emissions. Three TGFs are analyzed here and confirm previous findings on the close association between TGF generation and lightning processes and, for the first time, provide time‐aligned measurements of the VHF radio signature within a few tens of microseconds of TGF generation. Strong VHF emissions were observed essentially simultaneously with two TGFs and within a few tens of microseconds of a third TGF. Equally importantly, the VHF measurement details indicate that the TGF‐associated emissions are nonimpulsive and extended in time. We conclude that the TGF‐producing process is at least sometimes closely associated with strong VHF emissions, and thus, there may be a link between the generation of TGFs and active lightning streamer dynamics. Plain Language Summary: Terrestrial gamma ray flashes (TGFs) are one of the highest‐energy natural photon emissions generated during thunderstorms. Many insights into the physical mechanism of TGFs were revealed by the coordinated observations of TGFs by ground‐based radio sensors. Here we presented observations of TGFs detected simultaneously by Fermi Gamma‐ray Burst Monitor, two very high frequency (VHF) lightning mapping arrays, and Duke ground‐based low‐frequency (LF) radio sensors. This is the first time that the temporal relationship between TGFs and VHF emissions is examined with such high precision. The three rather different signatures of these LF signals highlight the complexity and differences from event to event of LF radio emissions associated with TGFs. Meanwhile, the VHF signature within a few tens of microseconds of TGFs was investigated and suggested that the TGF‐producing process at least sometimes also radiates brightly at VHF. More importantly, VHF emissions associated with TGFs have some surprisingly consistent features, namely, relatively high power, nonimpulsive, and probably extended source emissions. Key Points: Simultaneous gamma‐ray and multiband radio measurements provide a more complete picture of the TGF generation processes The TGF‐generating process is closely associated with strong and nonimpulsive VHF emissions The production of all three observed TGFs was accompanied by active lightning streamer zone dynamics